Impact of COVID-19 pandemic on emergency and elective surgery. A retrospective observational analysis in Apulia, southern Italy - Bianchi, Francesco Paolo; Daleno, Antonio; Rizzi, Donato; Migliore, Giovanni; Tafuri, Silvio (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. In Italy, at the beginning of the COVID-19 pandemic, only emergency and life-saving elective surgical procedures were allowed with obvious limitations in terms of numbers of operable cases. The aim of our study is to evaluate the performance of surgical activities by Apulian healthcare facilities (Southern Italy) under the pandemic emergency pressure.Methods. The surgical procedures in study were identified via the Apulian regional archive of hospital discharge forms. We used the ICD9 codes in order to define the elective and urgency surgeries in analysis, and we extended our search to all procedures performed from 2019 to 2021.Results. The number of all procedures decreased from 2019 to 2020; the reduction was higher for elective surgery (-43.7%) than urgency surgery (-15.5%). In 2021, an increase compared to 2020 was recorded for all procedures; nevertheless, elective surgeries registered a further slightly decrease compared to 2019 (-12.4%), while a slightly increase was observed for urgency surgeries (+3.5%). No particular variation was observed considering sex and age at surgery of the patients, and days of hospitalization from 2019 to 2021.Conclusions. The impact of COVID-19 on Apulian regional health system has been extremely shocked and has required the implementation of strategies aimed at containing the infection and guaranteeing health services as far as possible. A new paradigm of hospital care for SARS-COV-2 patients in the post-emergency phase in Italy is needed, in order to optimize the resources available and to guarantee high standards of quality and efficiency for citizens.